Does the teaching profession still need universities? - Furlong, J (Springer Netherlands, 2009)
Throughout his career, a core theme running through Eric Hoyle's writing has been his concern with the development of the teaching profession. Building on the work of classic American sociologists such as Everett Hughes and D.C. Lortie, for over 30 years Hoyle has been an observer, commentator and analyst of the teaching profession in England, highlighting advances, challenges and contradictions in the profession's changing fortunes. One factor that Hoyle has consistently seen as important in his analysis of the profession is its changing relationship with universities. From his earliest writings (Hoyle, 1974), Hoyle has considered universities important for the advancement of the teaching profession for two, closely interrelated reasons. Firstly they are important because they contribute to the process of 'professionalization'. Drawing his analysis from the sociology of the professions, Hoyle has argued that professionalization is an essentially political process; it is concerned with the advancement of the status of a profession. Because of their own status in society, a close association with universities, for initial training, for continuing professional development and for research, can therefore contribute to the political advancement of the teaching profession, helping to legitimate the status of its professional knowledge. © 2008 Springer Science+Business Media B.V.